Prognostic Value of the Persistence of C1q-Binding Anti-HLA Antibodies in Acute Antibody-Mediated Rejection in Kidney Transplantation. Issue 4 (April 2018) - Bailly, Elodie; Anglicheau, Dany; Blancho, Gilles; Gatault, Philippe; Vuiblet, Vincent; Chatelet, Valérie; Morelon, Emmanuel; Malvezzi, Paolo; Parissiadis, Anne; Tourret, Jérôme; Guidicelli, Gwendaline; Sayegh, Johnny; et al.
Abstract : Background: The differential pathogenicity of anti-HLA donor-specific antibodies (DSAs) is not fully understood. The presence of complement-binding DSAs helps in better defining the prognosis of acute antibody-mediated rejection (ABMR). The evolution of these antibodies after the treatment of ABMR is unknown. Methods: We included patients from the French multicenter RITUX ERAH study diagnosed with acute ABMR within the first year of renal transplantation, with circulating anti-HLA DSAs and treated randomly by rituximab or placebo (and intravenous immunoglobulins, plasma exchange). We centrally analyzed serum samples at the time of ABMR, 3 and 6 months after ABMR, with anti-HLA DSAs specificities and C1q-binding capacity assessment. Results: Twenty-five patients were included: 68% had C1q-binding DSAs at the time of ABMR. The presence of C1q-binding DSAs was associated with a poorer evolution of chronic glomerulopathy at 6 months ( P = 0.036). The persistence of C1q-binding DSAs at 3 and/or 6 months after ABMR was associated with more severe chronic glomerulopathy ( P = 0.006), greater C4d score deposition score at 6 months after ABMR ( P = 0.008), and graft loss 5 years after ABMR ( P = 0.029). C1q-binding capacity was associated with the DSA MFI but 5 C1q-binding DSAs in 4 patients had low MFI values without a prozone effect. Conclusion: The presence and persistence of anti-HLA C1q-binding DSAs after ABMR is a detrimental marker, leading to transplant glomerulopathy and graft loss. Assessment of the complement-binding capacities of DSAs could help decide treatment intensification. Abstract : The presence and persistence of anti-HLA C1q-binding anti-HLA donor-specific antibodies (DSAs) after acute antibody-mediated rejection is a detrimental marker, leading to transplant glomerulopathy and graft loss and assessment of the complement-binding capacities of DSAs could help decide treatment intensification.